Maternal Sleeping Problems Before and After Childbirth - A Systematic Review - Witkowska-Zimny M; Zhyvotovska A; Isakov R; Boiko DI; Nieradko-Iwanicka B (Dove Medical Press, 2024)
Malgorzata Witkowska-Zimny,1,* Anastasiia Zhyvotovska,2,* Rustam Isakov,2 Dmytro I Boiko,2 Barbara Nieradko-Iwanicka3 1Department of Human Anatomy, Medical University of Warsaw, Warsaw, Poland; 2Department of Psychiatry, Narcology and Medical Psychology, Poltava State Medical University, Poltava, Ukraine; 3Chair and Department of Hygiene and Epidemiology, Medical University of Lublin, Lublin, Poland*These authors contributed equally to this workCorrespondence: Malgorzata Witkowska-Zimny, Department of Human Anatomy, Medical University of Warsaw, 5 Chalubinskiego Str., Warsaw, 02-004, Poland, Email mwitkowska@wum.edu.pl Anastasiia Zhyvotovska, Department of Psychiatry, Narcology and Medical Psychology, Poltava State Medical University, 1 Medychna Str., Poltava, 36013, Ukraine, Email jyvotovskaaa@gmail.comAbstract: The perinatal and postpartum period is of great significance for women due to physiological changes, shifts in circadian rhythms, social setting, and psychological well-being, all of which affect the quality and quantity of their sleep. A mixed-studies systematic review was undertaken to enhance our understanding of sleep disturbances and mood disorders in women in late pregnancy and the postpartum period, their connection with breastfeeding, and the assessment of interventions for sleep disturbance. Three electronic databases (PUBMED, EMBASE and Google Scholar) were searched for qualitative, observational, and mixed-method studies from the year 2016 to June 2023. Twenty-nine articles were included in the analysis. The results were synthesized into four overarching themes: (і) the sleep quality of women in the perinatal period; (ii) the relationship between sleep and breastfeeding; (iii) the relationship between sleep quality and emotional disturbance in the perinatal period; (iv) sleep interventions in the researched group. The subjective nature of the perception of sleep disturbances, along with the absence of an objective measurement tool is clearly an inconvenience. It is advisable to include the assessment of maternal sleep hygiene and family sleep patterns during postpartum healthcare provider appointments to develop strategies not only for women's sleep quality but also for their mental well-being.Keywords: childbirth, breastfeeding, maternal sleep, sleep quality, sleep disturbance, psycho-emotional states